Analisis Kebutuhan Pengembangan Modul Psikoedukasi Kesehatan Mental sebagai Media Layanan Bimbingan Konseling Siswa SMP di Surakarta: Needs Analysis for the Development of a Mental Health Psychoeducation Module as a Medium for Student Guidance and Counseling Services in Surakarta Junior High Schools - Tika Mustikawati; Sunardi Sunardi; Eka Budhi Santosa (ITScience (Information Technology and Science), 2026)
Mental health issues among adolescents are on the rise, yet adequate levels of mental health literacy have not matched this trend. This situation is exacerbated by limited mental health education services and a scarcity of learning materials designed to enhance students' understanding. This study aimed to conduct a needs analysis for the development of a mental health psychoeducation module to serve as a resource for Guidance and Counselling services for junior high school students. A qualitative descriptive approach with a needs assessment design was employed. The participants consisted of 31 seventh-grade students and one Guidance and Counselling teacher from SMP Negeri 20 Surakarta. Data collection involved observation, questionnaires, and in-depth interviews, with the data subsequently analysed using the Miles, Huberman, and Saldaña framework, which comprises three key stages: data condensation/reduction, data display, and final verification. The needs analysis indicated that developing a Mental Health Psychoeducation Module is a priority, as there is currently a lack of psychoeducational materials to support Guidance and Counselling services in improving students' mental health literacy in a manner aligned with their specific characteristics and needs. The findings confirm that developing a psychoeducational module based on student needs is a strategic step toward supporting Guidance and Counselling services while simultaneously enhancing mental health literacy.